2003
DOI: 10.2478/bf02475230
|View full text |Cite
|
Sign up to set email alerts
|

Wittig and Wittig-Horner reactions under phase transfer catalysis conditions

Abstract: Wittig and Wittig-Horner reactions are favorite tools in preparative organic chemistry. These ole nation methods enjoy widespread and recognition because of their simplicity, convenience, and e¯ciency. Phase transfer catalysis (PTC) is a very important method in synthetic organic chemistry having many advantages over conventional, homogenous reaction procedures. In this paper, we attempt to summarize the aspects concerning Wittig and Wittig-Horner reactions that take place under phase transfer catalysis condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…The reaction between p -methoxybenzaldehyde (PMBD) and benzyltriphenylphosphonium bromide ([Ph 3 P-CH 2 -Ph] + Br – , BTPPB) to yield 1-methoxy-4-styrylbenzene (MSYB) is considered in the present work as the model PTC Wittig reaction. This biphasic reaction is classified as a phase-transfer-catalyzed (PTC) reaction even though the BTPPB itself serves as one of the reactants …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction between p -methoxybenzaldehyde (PMBD) and benzyltriphenylphosphonium bromide ([Ph 3 P-CH 2 -Ph] + Br – , BTPPB) to yield 1-methoxy-4-styrylbenzene (MSYB) is considered in the present work as the model PTC Wittig reaction. This biphasic reaction is classified as a phase-transfer-catalyzed (PTC) reaction even though the BTPPB itself serves as one of the reactants …”
Section: Methodsmentioning
confidence: 99%
“…The Wittig reaction is one of the most powerful and versatile approaches in the fine chemical and pharmaceutical industries to access alkenes from ketones or aldehydes with unambiguous positioning of the carbon−carbon double bond. 1 In this reaction, the alkyl-substituted phosphonium salt is deprotonated by a strong base to yield the phosphonium ylide, which then subsequently reacts with ketone or aldehyde to afford olefin and phosphine oxide (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…8 Rathke and Nowak extended these studies in 1985 and reported that the use of LiBr or MgBr 2 and triethylamine leads to a conversion of aldehydes and ketones with similar yields to those reactions reported with strong bases. 9 These studies triggered a cascade of explorations to optimize the conditions for HWE reactions (phase transfer catalyst, 10 microwave irradiation, metal-promoted HWEs), 11 selectivity (enantioselective or diastereoselective transformations), 12 and substrate scope. While these seminal findings unraveled the correlation of acidity, complexation, and reactivity in phosphonate-based olefination reactions, they also stimulated the usage of other heteroatom-stabilized carbanions.…”
Section: Review Synthesismentioning
confidence: 99%
“…Reported green synthetic methods included reaction system with ionic liquid or water [5][6][7] as solvent, phase-transfer catalytic (PTC) system [8], no solvent system [9], reaction system with the help of microwave [10][11][12] or ultrasonic wave [13,14], and base-free system [15]. However, above systems mainly involved "moderately acidic" and "acidic" phosphonate, which pK a value was lower than 23, such as ␤-keto phosphonate, 1-butyl-2,3-dimethylimidazolium hexafluoroph osphate and ethyl (diethyl phosphono) acetate.…”
Section: Introductionmentioning
confidence: 99%